A study of Total Quality Management (TQM) practices towards employees’ awareness in Perbadanan Kemajuan Negeri Melaka (PKNM) / Hanee Nazyah Ahmad Moghni - Ahmad Moghni, Hanee Nazyah (Faculty of Business and Management, 2010)
This research is about a study of total quality management (TQM) practices towards employees’ awareness In Perbadanan Kemajuan Negeri Melaka (PKNM). The factors of TQM practices such as leadership, employees’ awareness and training have been identified to investigate whether or not these factors influence the awareness of the employees. The survey was conducted in PKNM. The sample size of this study was 30 respondents who are the employees of the organization. Data was obtained using primary data. Respondents were required to answer the questionnaires that included the statements of each variable. Once the necessary data was collected, the data was analyzed and summarized in a readable and easily interpret form. The Statistical Package for the Social Science (SPSS) version 16 was used to summarize the data. The results are in form of reliability testing, descriptive statistic, T-test and correlation. Based on this research, the result indicates that all the factors of the TQM practices are correlated where it refer that there are significant relationship between independent variables (leadership and training) and dependent variables (employees’ awareness). However, there is no significant relationship between employees’ empowerment and employees’ awareness. The conclusion of the study is the outcome of the survey analysis and findings. Finally, on the findings, some recommendations have been suggested in order to improve the understanding on how the employees can enhance the TQM practices in PKNM.